Communication About Micropollutants in Drinking Water: Effects of the Presentation and Psychological Processes. Issue 10 (15th September 2015) - Tobias, Robert
Abstract : This study investigates how people change their risk perception, trust, and behavior as a consequence of being informed about the occurrence of micropollutants in drinking water. Micropollutants are substances present in extremely low concentrations that might be dangerous in higher concentrations. Data were gathered in the city of Zurich, Switzerland in 2013 using a questionnaire in which the information on micropollutants was presented differently to 12 experimental groups. Data of the key constructs were gathered before and after this information, so that causal effects could be quantified by regression analyses. Affective reactions to the information turned out to be the critical mediator of changes in risk perception (operationalized as the perceived change of quality due to pollution), which is an important determinant of changes in behavior and trust. Also, direct effects of affective reactions on behavior and trust were observed. Trust before appraising risks reduces negative affective reactions; however, it also reduces perceived quality (i.e., increases risk perception) and trust after risks are appraised. The different forms of information mainly influenced the participants' affective reactions, but they also influenced perceived quality. The presentation with the least negative effects was a comparison of the intake of the substance by water with intake by food. The experimental design with repeated measurement that considers trust as a determinant and consequence of risk perception uncovered positive and negative effects of trust before appraising risks on changes of risk perception and trust due to appraising risks.